The Effect of Business Capital, Financial Technology and Financial Literacy on MSMEs’ Sustainability - Kukuh Esty Sesanty; Siti Resmi; Alivia Meyrizka Utami; Helena Yovita Junijanto (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study investigates the impact of business capital, financial literacy, and financial technology on the sustainability of MSMEs in Bantul Regency. Data collection was conducted through a survey and distributed to respondents. This study involved a sample of 102 MSMEs in Bantul Regency that had been operating for at least 2 years and used a digital payment system as a means of payment. As to the study's findings, MSMEs' sustainability is negatively impacted by business capital, negatively impacted by financial technology, and positively impacted by financial literacy. The research is expected to contribute to UMKM actors to increase knowledge about business capital and financial technology which is a very important thing to prioritize. In addition, UMKM actors must continue to participate in mentoring and business coaching that focuses on capital and financial technology so that they can guarantee business sustainability.